2021
DOI: 10.1021/acs.jmedchem.1c01294
|View full text |Cite
|
Sign up to set email alerts
|

New Design Rules for Developing Potent Cell-Active Inhibitors of the Nucleosome Remodeling Factor (NURF) via BPTF Bromodomain Inhibition

Abstract: The nucleosome remodeling factor (NURF) alters chromatin accessibility through interactions with its largest subunit,the bromodomain PHD finger transcription factor BPTF. BPTF is overexpressed in several cancers and is an emerging anticancer target. Targeting the BPTF bromodomain presents a potential strategy for its inhibition and the evaluation of its functional significance; however, inhibitor development for BPTF has lagged behind those of other bromodomains. Here we describe the development of pyridazinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…1b ). These are of interest for targeted therapeutics 30 , and so an understanding of their function is critical. In the context of histone peptides, the PHD finger (PHD) has been shown to associate with H3 tri-methylated at lysine 4 (H3K4me3) 28 , while the bromodomain (BD) binds to histone tails containing acetylated lysines, with a preference for the acetylated H4 tail 3133 .…”
Section: Bptf Phd-bd Demonstrates Restricted Specificity and Synergis...mentioning
confidence: 99%
“…1b ). These are of interest for targeted therapeutics 30 , and so an understanding of their function is critical. In the context of histone peptides, the PHD finger (PHD) has been shown to associate with H3 tri-methylated at lysine 4 (H3K4me3) 28 , while the bromodomain (BD) binds to histone tails containing acetylated lysines, with a preference for the acetylated H4 tail 3133 .…”
Section: Bptf Phd-bd Demonstrates Restricted Specificity and Synergis...mentioning
confidence: 99%
“…We further characterized our compounds for ternary complex formation and degradation of full-length BRD9 using NanoBRET. BRD9 is a reported offtarget for the pyridazinone scaffold 12,34 and TP-238. 25 Due to its smaller size (75 kDa) compared to full-length BPTF (~300 kDa), we expected full-length BRD9 (BRD9-FL) to be more amenable to transfection and easier to study in this assay compared to full-length BPTF.…”
Section: Resultsmentioning
confidence: 99%
“…11 However, for many non-BET bromodomains, it remains unclear whether bromodomain inhibition alone will be effective to induce a significant phenotypic effect. In the case of BPTF, we 12 and others 13 have shown that bromodomain inhibitors when used as single agents may be insufficient for anticancer therapeutic applications. We previously reported that BPTF inhibitors sensitize 4T1 breast cancer cells to the chemotherapeutic, doxorubicin.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations